1990
DOI: 10.1002/1097-0142(19900401)65:7<1577::aid-cncr2820650721>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Is DNA ploidy an independent prognostic indicator in infiltrative node-negative breast adenocarcinoma?

Abstract: To evaluate DNA content as an independent, long-term prognostic indicator in infiltrative, node-negative adenocarcinoma of the breast, flow cytometric DNA analyses were performed retrospectively in 165 patients. The exclusive use of paraffin-embedded tissue permitted the study of patients for whom 3 to 15 years' follow-up was available. Other investigators have shown a relationship between DNA nuclear content and well-known prognostic indicators of breast carcinoma, such as estrogen receptors, age, menopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 27 publications
4
9
0
2
Order By: Relevance
“…Reports on the prognostic value of ploidy status as determined by flow cytometry have been inconsistent (see review by Frierson [15]). In studies where overall survival was followed up for periods comparable with that in the present investigation, significantly better survival rates have been found for diploid cases than for nondiploid cases by Kallioniemi et al [16], Toikkanen et al [17], and Lewis [18], whereas, like us, Beerman et al [19], Muss et al [20], and Keyhani-Rofaga et al [21] found no significant difference in survival between diploid and non-diploid node-negative cases. In node-positive cases, Kallioniemi et al [16] and Beerman et al [19] found diploid cases to manifest significant survival advantage, whereas, like us, Toikkanen et al [ 17] did not.…”
Section: Dna Flow Cytometry and Er In Prognosis 123supporting
confidence: 74%
“…Reports on the prognostic value of ploidy status as determined by flow cytometry have been inconsistent (see review by Frierson [15]). In studies where overall survival was followed up for periods comparable with that in the present investigation, significantly better survival rates have been found for diploid cases than for nondiploid cases by Kallioniemi et al [16], Toikkanen et al [17], and Lewis [18], whereas, like us, Beerman et al [19], Muss et al [20], and Keyhani-Rofaga et al [21] found no significant difference in survival between diploid and non-diploid node-negative cases. In node-positive cases, Kallioniemi et al [16] and Beerman et al [19] found diploid cases to manifest significant survival advantage, whereas, like us, Toikkanen et al [ 17] did not.…”
Section: Dna Flow Cytometry and Er In Prognosis 123supporting
confidence: 74%
“…However, at this time, tumor size and lymph node status remain the most important prognostic factors in patients with early stage breast carcinoma. [12][13][14][15][16][17][18] It should be noted that in a study of mammographically detected tumors that pathologically measured Ͻ 1.0 cm in size the incidence of axillary lymph node metastasis was 3%, 24 which is similar to our finding of no positive lymph nodes in the 15 patients with small, mammographically detected breast carcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…5,10 There 10 Paraffin 165 P Ͻ 0.0001 a Muss 16 Frozen 101 51 NS NS NS NS Clark et al 11 Frozen 345 59 P ϭ 0.02 NS P ϭ 0.02 NS Clark et al 11 Paraffin 298 b NS NS Toikkanen et al 12 Paraffin 158 336 P ϭ 0.01 NS Sigurdsson et al 18 250 48 NS NS O'Reilly et al 19 Paraffin 136 c 96 NS Beerman et al 20 Frozen/paraffin 349 84 NS Keyhani-Rofagha et al 21 Paraffin 165 103 NS Winchester et al 22 Paraffin 257 80 NS NS Merkel et al 23 Paraffin 280 76 NS Balslev et al 13 Frozen 10 demonstrated DNA ploidy to have a prognostic significance in ER-positive tumors, but not in ER-negative tumors, in patients with stage I-III breast cancer. In the present study, multivariate analysis showed the prognostic significance of DNA ploidy, in terms of DFS, in ER-positive breast cancer specimens, but not in ER-negative breast cancer specimens.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The prognostic value of DNA ploidy has also been extensively studied in Western women with node-negative breast cancer; however, the results have not been consistent. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Some studies have shown that patients with aneuploid tumors have a significantly worse clinical outcome, [9][10][11][12][13][14][15] whereas others have shown DNA ploidy to have no prognostic value. [16][17][18][19][20][21][22][23] A few studies have reported the relationship between DNA ploidy and the clinical outcome in Japanese patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%